2013
DOI: 10.1016/j.worlddev.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Food Security, Gender, and Occupational Choice among Urban Low-Income Households

Abstract: Rising urban poverty and food insecurity are serious concerns in developing countries today. Urban livelihoods and coping strategies remain poorly understood however. This paper examines the response of female and male household members in marginalized urban (predominantly squatter) areas to the risk of food shortage in terms of occupational choice. More specifically, we use probit analyses to investigate whether household vulnerability or the need to provide self-insurance for food security, alongside gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 34 publications
1
48
0
5
Order By: Relevance
“…In Hovorka et al [51], the role of women in feeding the urban population was emphasized, with women contributing to food security through activities like urban farming amongst others. Floro and Swain [19] reported that women from urban low-income households were engaging in food enterprises and earn money income to be used as a direct source of food for consumption. The work of Schindler [52] discussed the use of credits by market women and reveals that oftentimes they invest more time to nature the relationship in order to secure access to credit once shocks occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hovorka et al [51], the role of women in feeding the urban population was emphasized, with women contributing to food security through activities like urban farming amongst others. Floro and Swain [19] reported that women from urban low-income households were engaging in food enterprises and earn money income to be used as a direct source of food for consumption. The work of Schindler [52] discussed the use of credits by market women and reveals that oftentimes they invest more time to nature the relationship in order to secure access to credit once shocks occur.…”
Section: Discussionmentioning
confidence: 99%
“…Women in vulnerable households, for example, were found to likely engage in food enterprises, where choice of business is associated with household vulnerability to food insecurity [19]. Urban low-income households were reported to select enterprises that earn them money to get food for consumption as a strategy to mitigate the risk of food shortages [19].…”
Section: Open Accessmentioning
confidence: 99%
“…Various agencies and individuals (Dutta, 2000;SAATH, 1995;SHARDA Trust, 1995-2001; SHARDA Trust & SAATH, 1999) have documented the impact of physical infrastructure for the Sanjaynagar settlement, which informed the current study. Women in vulnerable households are likely to be engaged in food enterprises, water collection, fuel wood collection and water disposal/cleaning activities (Floro & Swain, 2013;UNDP, 2006). Estimates by SEWA show that reducing water collection duration from two to one hour a day would enable women to earn an additional US$ 100/year (UNDP, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, there is institutionalised gender bias against the education of female children in India (Dercon & Singh, 2013). Women bear the brunt of inadequate infrastructure provision as they have to spend time on water collection, waste disposal and collection of fuel wood for energy provision (Floro & Swain, 2013;Parikh, Chaturvedi & George, 2012;UNDP, 2006). In Indian slums, girls spend time for water collection in lieu of attending school, resulting in gender imbalances in education levels.…”
Section: Introductionmentioning
confidence: 99%
“…For example, landlockedness, farness from a large market, and low levels of human resources tend to be serious handicaps to growth, but are not elements of vulnerability because they are not unforeseen events, however they may influence the consequences of a given shock (Vial & Hanoteau, 2015). The researcher furthered the study and provided two main reasons for households to get involved in a micro-enterprise, which are to increase their income and consumption, in order to cope with economic vulnerability (Floro & Swain, 2013;Verrest, 2013). This reason enables a micro-enterprise to diversify a family's sources of income, and boost it for the purpose of saving as mentioned by Verrest (2013).…”
Section: Economic Vulnerabilitymentioning
confidence: 99%